2019
DOI: 10.1055/s-0039-1685514
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Screw Length on Proximal Scaphoid Fracture Biomechanics

Abstract: Background Proximal scaphoid fractures display high nonunion rates and increased revision cases. Waist fracture fixation involves maximizing screw length within the cortex; however, the optimal screw length for proximal scaphoid fractures remains unknown. Purpose The main purpose of this article is to compare stiffness and ultimate load for proximal scaphoid fracture fixation of various headless compression screw lengths. Methods Eighteen scaphoids underwent an osteotomy simulating a 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…It is crucial to find the best screw sizes for surgical outcomes, especially in patients with scaphoid nonunion, where we use a radiograph of the normal side to evaluate screw length. 1,2 In surgical cases, the inserted guidewire measures scaphoid 5.5 (0.9) 5.5 (0.9) 5.5 (0.9) 0.9 SL ratio 1.9 (0.2) 1.9 (0.2) 1.9 (0. 2), and 5.5 (0.9) mm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is crucial to find the best screw sizes for surgical outcomes, especially in patients with scaphoid nonunion, where we use a radiograph of the normal side to evaluate screw length. 1,2 In surgical cases, the inserted guidewire measures scaphoid 5.5 (0.9) 5.5 (0.9) 5.5 (0.9) 0.9 SL ratio 1.9 (0.2) 1.9 (0.2) 1.9 (0. 2), and 5.5 (0.9) mm.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the standard lengths and widths of the scaphoid at different levels may be beneficial for inventory management in the operating room during scaphoid fracture management, in instances where screw placement is required, and in nonunion. 1,2 Several measurements and indices, such as the scapholunate (SL) angle, the scaphoid lunate ratio, and the SL gap, have been used to quantify and diagnose carpal instability. [3][4][5] The radioscaphoid angle has been recognized as a quantifiable measure for assessing outcomes in intercarpal arthrodesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in a shorter screw in this study that could affect the fixation strength. However, Patel et al demonstrated maximizing screw length may not provide superior fixation for proximal scaphoid fractures [20]. Therefore, a 2 mm gap at the fracture site that simulated a scaphoid waist fracture may have been the reason for inferior fixation strength.…”
Section: Discussionmentioning
confidence: 99%
“…Headless compression screws represent the current gold standard in the surgical treatment of scaphoid fractures and non-unions [4][5][6]. High failure rates have been in part attributed to insufficient screw characteristics and unfavourable placement [5][6][7]. The technical features of the screw determine the tensile force that is required to reach the point of failure to screw pull-out [3].…”
Section: Introductionmentioning
confidence: 99%